‘Blue waves versus political tsunami’: Sarawak and the 2008 Malaysian General Election. - Neilson Ilan Mersat (Universiti Kebangsaan Malaysia, 2009)
The 2008 general election was a disastrous outing for the National Front (Barisan Nasional). The party not only failed to retain two third of the seats in the national parliament but lost five states to the opposition. The defeat was attributed to strong opposition politics which had created ‘political tsunami’ of sorts and swept across several states which were formerly BN’s stronghold. The defeat in several states also marked the end of BN’s hegemony. It begs the question of whether BN is still relevant. Ironically Sarawak remained a bastion of BN and the party won all the parliamentary seats except one. BN’s win in Sarawak was likened to a ‘blue waves’ (blue is the colour for BN’s flags) that like ‘political tsunami’ in Peninsular Malaysia had swept away all the opposition candidates except for Bandar Kuching. However, despite the big win in term of seats the support for BN in the urban areas declined greatly with some of its candidates won with a slim majority. This article examines the contestation between ‘blue waves’ and ‘political tsunami’ in Sarawak during the 2008 elections. The contestation is examined in the contexts of ‘politics of developmentalism’, which really impacted the electoral outcome in the rural areas. ‘Politics of developmentalism’ is put into practice by using government projects as patronage tools for sustaining and securing political support. This strategy works well especially in the rural areas where politics is still very much driven by the urge to fulfill basic needs.